Changes in physical and chemical characteristics of fermented cocoa (Theobroma cacao) beans with manual and semi-mechanized transfer, between fermentation boxes - Peláez, Pedro. P. (2016)
The aim of this study was to evaluate variation in the physical and chemical properties of fermented cocoa beans with cocoa beans transfer between wooden fermentation boxes manually (M) and semi-mechanized (SM) way. Mass temperature, moisture, pH, and total acidity of the cotyledon and pulp; the total polyphenol, anthocyanin, reducing sugar, theobromine, and caffeine content in fresh, fermented, and dried beans; and percentage of fermented beans and time required to move beans during fermentation were determined. The cocoa used grew in the Pachiza district of the San Martin region of Peru. Cocoa sampling was each 0, 48, 72, 96, 120, 144, and 168 h of fermentation. The cocoa mass temperature was highest with both removal systems after 96 h of fermentation. M cotyledon and pulp samples had the highest moisture content and titratable acidity, while cotyledon and pulp pH with both systems were statistically equal. In contrast, fermented beans had a higher polyphenol, anthocyanin, reducing sugar, theobromine, and caffeine content with SM. SM produced the greatest amount of fermentation (91.67%) and required the shortest amount of time to move beans (78.56 min). In conclusion, the system of fermentation of cocoa beans with SM was faster and produced fermented grains with high chemical quality.